Breeding of NHase hyper-producing Rhodococcus ruber strain LUV30-06 and verification of mutants by RAPD - Wang, Shiwei; Wang, Min; Wang, Qinghui (Scientific Research Publishing, 2013)
A nitrile hydratase (NHase) hyper-producing Rhodococcus ruber strain LUV30-06 was bred by mutagenization on the starting strain CGMCC3090 with ultraviolet irradiation and lithium chloride. The NHase activity of the strain LUV30-06 was increased by 21.99% (3881.3 U/ml), as compared with that of R. ruber CGMCC3090 (3181.4 U/ml). The mutant strain UV30-06 has been proved genetically stable with higher NHase activity in seven successive subcultures as well as random amplified polymorphic DNA analysis (RAPD).
Keywords: Rhodococcus ruber; NHase; Mutagenesis; Random Amplified Polymorphic DNA